1996
DOI: 10.1093/oxfordjournals.annonc.a010500
|View full text |Cite
|
Sign up to set email alerts
|

Single agent activity of oxaliplatin in heavily pretreated advanced epithelial ovarian cancer

Abstract: The 29% ORR single agent activity of oxaliplatin at hematological subtoxic doses in heavily pretreated ovarian cancer patients, with objective responses in platinum refractory patients, supports experimental data on non cross-resistance and a differential clinical toxicity profile to other available platinum compounds. The 12 month median overall survival of this poor prognosis patients cohort (62% platinum-refractory patients, median number of three previous chemotherapy lines) gives a strong empirical basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(56 citation statements)
references
References 13 publications
1
53
0
2
Order By: Relevance
“…In our study of the H69 SCLC cells, oxaliplatin did not have activity against the cisplatin-resistant H69CIS200 cells and there are similar reports in ovarian carcinoma [40]. This also complements the clinical studies showing a lack of activity of oxaliplatin in cisplatin resistant ovarian carcinoma [17][18][19]. Our study questions the effectiveness of oxaliplatin in cisplatin resistant cancer and suggests that more research into the mechanisms of low-level platinum resistance is needed to resolve this issue.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our study of the H69 SCLC cells, oxaliplatin did not have activity against the cisplatin-resistant H69CIS200 cells and there are similar reports in ovarian carcinoma [40]. This also complements the clinical studies showing a lack of activity of oxaliplatin in cisplatin resistant ovarian carcinoma [17][18][19]. Our study questions the effectiveness of oxaliplatin in cisplatin resistant cancer and suggests that more research into the mechanisms of low-level platinum resistance is needed to resolve this issue.…”
Section: Discussionsupporting
confidence: 80%
“…Platinum pre-treated patients and clinical platinum resistance are not necessarily the same and different criteria are used in different clinical trails. When oxaliplatin was studied as a single agent in ovarian carcinoma where patients were divided into platinum resistant or platinum sensitive based on Markman's criteria [16], there was a clear drop in response rate to oxaliplatin in the cisplatin resistant patients [17][18][19]. This suggests that oxaliplatin's activity is reduced in cisplatin resistant cancer as this cohort failed to respond to oxaliplatin as a single agent.…”
Section: Introductionmentioning
confidence: 99%
“…Oxaliplatin has a more manageable toxicity profile than cisplatin, with no renal toxicity and a lower incidence of haematological and gastrointestinal toxicities. It lacks the nephrotoxicity of cisplatin and causes less myelotoxicity than carboplatin, the leading cisplatin analog, and it may be active in cisplatin-and carboplatin-resistant tumours (Chollet et al, 1996;Raymond et al, 1998b). The main toxicity associated with oxaliplatin is a generally reversible peripheral neuropathy (Raymond et al, 1998a).…”
mentioning
confidence: 99%
“…In combination with 5FU/leucovorin, it represents the preferential first-line regimen in the management of CRC in both adjuvant [81] and metastatic [82] settings. With respect to EOC, phase II studies with single agent oxaliplatin have reported an overall response rate (ORR) of 5.6-17% and 42-46% with single agent oxaliplatin in platinum resistant and platinum sensitive disease respectively [83,84].…”
Section: Oxaliplatinmentioning
confidence: 99%